1998
DOI: 10.1029/97jd03376
|View full text |Cite
|
Sign up to set email alerts
|

An ion‐molecule mechanism for the formation of neutral sporadic Na layers

Abstract: Abstract. This paper describes a laboratory study into the chemical pathways by which Na + is converted to Na in the upper atmosphere. The termolecular clustering reactions of Na + with shown that atomic O will ligand switch with Na. N2 + but not with Na. CO2 +, and that the former reaction proceeds essentially at the Langevin collision frequency. The neutralization of Na + in the upper atmosphere is therefore rather complex. The first step is formation of the Na. N2 + ion from the recombination of Na + with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
163
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(172 citation statements)
references
References 62 publications
8
163
1
Order By: Relevance
“…Furthermore, the recombination rate of molecular ions increases with decreasing altitude and the chemical equilibrium between ions and atoms tends towards a larger share of atoms with decreasing altitude. Similarly, the chemistry-based model studies of Cox and Plane (1998) for the formation of sporadic Na layers confirm the role of dissociative recombination of molecular ions for forming Na atoms. The delayed conversion of Ca + ions into Ca atoms leads us to expect that the lidar will be able to detect simultaneous neutral Ca s layers at the altitudes of only those Ca + s layers which were either strong or long-lasting (see Fig.…”
Section: Interpretation Of Variations and Implications For The Formatmentioning
confidence: 81%
“…Furthermore, the recombination rate of molecular ions increases with decreasing altitude and the chemical equilibrium between ions and atoms tends towards a larger share of atoms with decreasing altitude. Similarly, the chemistry-based model studies of Cox and Plane (1998) for the formation of sporadic Na layers confirm the role of dissociative recombination of molecular ions for forming Na atoms. The delayed conversion of Ca + ions into Ca atoms leads us to expect that the lidar will be able to detect simultaneous neutral Ca s layers at the altitudes of only those Ca + s layers which were either strong or long-lasting (see Fig.…”
Section: Interpretation Of Variations and Implications For The Formatmentioning
confidence: 81%
“…Cox and Plane (1998) suggested an ion-molecule formation mechanism for sporadic Na layers, that was tested experimentally by Heinselman et al (1998) and Heinselman (2000). Clemesha et al (1999) concluded the ion-recombination mechanism to be the most likely cause for sporadic Na layers.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Whether or not these structures result in the formation of what would conventionally be called a sporadic layer would depend on the amplitude and, perhaps more importantly, the coherence of the wave responsible. In summary, we suggest that the following process takes place: sodium ions, trapped at the descending nodes in the winds associated with tides and/or gravity waves, are neutralized by processes of the sort described by Cox and Plane [1998], leading to the formation of descending peaks in sodium density. When the amplitude and coherence of the waves are appropriate, this process can lead to the formation of the narrow layers of very high density known as sporadic layers.…”
Section: Discussionmentioning
confidence: 99%